AI Research Funding Portfolios and Extreme Growth - Rahkovsky, Ilya; Toney, Autumn; Boyack, Kevin W.; Klavans, Richard; Murdick, Dewey A. (Frontiers in Research Metrics and Analytics, 2021)
Our work analyzes the artificial intelligence and machine learning (AI/ML) research portfolios of six large research funding organizations from the United States (National Institutes of Health (NIH) and National Science Foundation (NSF)); Europe (European Commission (EC) and European Research Council (ERC)); China (National Natural Science Foundation of China (NNSFC)); and Japan (Japan Society for the Promotion of Science (JSPS)). The data for this analysis is based on 127 thousand research clusters (RCs) that are derived from 1.4 billion citation links between 104.8 million documents from four databases (Dimensions, Microsoft Academic Graph, Web of Science, and the Chinese National Knowledge Infrastructure). Of these RCs, 600 large clusters are associated with AI/ML topics, and 161 of these AI/ML RCs are expected to experience extreme growth between May 2020 and May 2023. Funding acknowledgments (in the corpus of the 104.9 million documents) are used to characterize the overall AI/ML research portfolios of each organization. NNSFC is the largest funder of AI/ML research and disproportionately funds computer vision. The EC, RC, and JSPS focus more efforts on natural language processing and robotics. The NSF and ERC are more focused on fundamental advancement of AI/ML rather than on applications. They are more likely to participate in the RCs that are expected to have extreme growth. NIH funds the largest relative share of general AI/ML research papers (meaning in areas other than computer vision, natural language processing, and robotics). We briefly describe how insights such as these could be applied to portfolio management decision-making.